Emotional Egocentricity Bias Across the Life-Span - Riva, Federica; Triscoli, Chantal; Lamm, Claus; Carnaghi, Andrea; Silani, Giorgia (Frontiers in Aging Neuroscience, 2016)
In our daily lives, we often have to quickly estimate the emotions of our conspecifics in order to have successful social interactions. While this estimation process seems quite easy when we are ourselves in a neutral or equivalent emotional state, it has recently been shown that in case of incongruent emotional states between ourselves and the others, our judgments can be biased. This phenomenon, introduced to the literature with the term Emotional Egocentricity Bias (EEB), has been found to occur in young adults and, to a greater extent, in children. However, how EEB changes across the life-span from adolescence to old age has been largely unexplored. In this study, we recruited 114 female participants subdivided in four cohorts (adolescents, young adults, middle-aged adults, older adults) to examine EEB age-related changes. Participants were administered with a paradigm which, by making use of visuo-tactile stimulation that elicits conflicting feelings in paired participants, allows the valid and reliable exploration of EEB. Results highlighted a U-shaped relation between age and EEB, revealing higher emotional egocentricity in adolescents and older adults compared to young and middle-aged adults. These results are in line with the neuroscientific literature which has recently shown that overcoming EEB is associated with a greater activation of a portion of the parietal lobe, namely the right Supramarginal Gyrus (rSMG). This is an area that reaches full maturation only by the end of adolescence, and displays an early decay in older age. Thus, the age-related changes of the EEB could be possibly due to the life-span development of the rSMG. This study is the first one to show the quadratic relation between age and the EEB and set a milestone for further research exploring the neural correlates of the life-span development of the EEB. Future studies are needed in order to generalize these results to the male population and to explore gender differences related to life-span changes in socio- emotional skills.